2012
DOI: 10.5194/acp-12-8389-2012
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric ozone trend over Beijing from 2002–2010: ozonesonde measurements and modeling analysis

Abstract: Abstract. Using a combination of ozonesonde data and numerical simulations of the Chemical Lagrangian Model of the Stratosphere (CLaMS), the trend of tropospheric ozone (O 3 ) during 2002-2010 over Beijing was investigated. Tropospheric ozone over Beijing shows a winter minimum and a broad summer maximum with a clear positive trend in the maximum summer ozone concentration over the last decade. The observed significant trend of tropospheric column ozone is mainly caused by photochemical production (3.1 % yr −1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
88
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 42 publications
3
88
1
Order By: Relevance
“…Ding et al (2008) studied the tropospheric ozone climatology over Beijing based on data from the MOZAIC (Measurement of Ozone and Water Vapor by Airbus InService Aircraft) program and found a 2 % year −1 increase of boundary layer ozone from the period of 1995-1999 to 2000-2005 over Beijing in the North China Plain (NCP) region and a weaker increasing trend of free-tropospheric ozone. Wang et al (2012) reported a similar increasing trend of lower tropospheric ozone and larger ozone increases in the middle and upper troposphere for the period of 2002-2010 based on ozonesonde measurements over Beijing. Ma et al (2016) found an increase of 1.1 ppbv year −1 for the period 2003-2015 in the maximum daily average 8 h concentration of ozone at Shangdianzi, a background site in the NCP.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Ding et al (2008) studied the tropospheric ozone climatology over Beijing based on data from the MOZAIC (Measurement of Ozone and Water Vapor by Airbus InService Aircraft) program and found a 2 % year −1 increase of boundary layer ozone from the period of 1995-1999 to 2000-2005 over Beijing in the North China Plain (NCP) region and a weaker increasing trend of free-tropospheric ozone. Wang et al (2012) reported a similar increasing trend of lower tropospheric ozone and larger ozone increases in the middle and upper troposphere for the period of 2002-2010 based on ozonesonde measurements over Beijing. Ma et al (2016) found an increase of 1.1 ppbv year −1 for the period 2003-2015 in the maximum daily average 8 h concentration of ozone at Shangdianzi, a background site in the NCP.…”
mentioning
confidence: 57%
“…The non-linear variation of ozone mixing ratio with season and many other meteorological factors can introduce uncertainties into the linear trend analysis. Wang et al (2012) de-seasonalised the monthly data by subtracting the average of all monthly data for a given month from the original data of the same month before performing a linear regression analysis. Oltmans et al (2006Oltmans et al ( , 2013 first performed an autoregressive model fitting incorporating explanatory variables (that are known sources of ozone variability) and a cubic polynomial fit to better represent the long-term variations of ozone, then used a bootstrap method to determine the trends of ozone.…”
mentioning
confidence: 99%
“…As the predominant source of OH, tropospheric O 3 controls the lifetime of CH 4 , CO, and VOCs, among many other air pollutants (Revell et al, 2015). In polluted regions, increased levels of O 3 are prevalent during seasons with stable high-pressure systems and intense photochemical processing of NO x and VOCs (Dentener et al, 2005;Xu et al, 2008) with downward transport from the stratosphere of lesser importance (Wang et al, 2012). By contrast, the main removal processes for tropospheric O 3 are chemical loss and dry deposition (Atkinson, 2000;Jenkin and Clemitshaw, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…From ozonesonde measurements, trends in the Indian troposphere and lower stratosphere were reported by Saraf and Beig (2004). These trends have been attributed to significant increase in anthropogenic emission of ozone precursors from South Asia during past couple of decades due to strong industrial and economic growth in this region (Beig et al 2008;Lal and Pawar 2011;Kulkarni et al 2010;Wang et al 2012;Ghude et al 2008;Krishnamurti et al 2009). To our knowledge, ozone trends in the UTLS region are not well studied over the India where significant transport of air from surface to UTLS through deep convection (Randel et al 2010) and STE occurs during monsoon season.…”
Section: Introductionmentioning
confidence: 99%
“…UTLS over Indian region has some unique features due to cross tropopause transport. For example, transport of boundary layer air into lower stratosphere due to strong Summer monsoon convection (Park et al 2009;Goswami et al 2006;Kunze et al 2010;Randel et al 2010;Chen et al 2012). Stratospheric intrusion during Winter and early pre-monsoon season (Fadnavis et al 2010) and cyclonic activity during premonsoon and post-monsoon seasons (Das et al 2011;Baray et al 1999;Sigmond et al 2000 The SAGE II data used here are based on the v6.2 retrieval algorithm.…”
Section: Introductionmentioning
confidence: 99%